The Rise of Inflow Cisternostomy in Resource-Limited Settings: Rationale, Limitations, and Future Challenges - Ulrick Sidney Kanmounye (Emergency Medicine International)
Low- and middle-income countries (LMICs) bear most of the global burden of traumatic brain injury (TBI), but they lack the resources to address this public health crisis. For TBI guidelines and innovations to be effective, they must consider the context in LMICs; keeping this in mind, this article will focus on the history, pathophysiology, practice, evidence, and implications of cisternostomy. In this narrative review, the author discusses the history, pathophysiology, practice, evidence, and implications of cisternostomy. Cisternostomy for the management of TBI is an innovation developed in LMICs, primarily for LMICs. Its practice is based on the cerebrospinal fluid shift edema theory that attributes injury to increased pressure within the subarachnoid space due to subarachnoid hemorrhage and subsequent dysfunction of glymphatic drainage. Early reports of the technique report significant improvements in the Glasgow Outcome Scale, lower mortality rates, and shorter intensive care unit durations. Most reports are single-center studies with small sample sizes, and the technique requires experience and skill. These limitations have led to criticisms and slow adoption of the technique. Further research is needed to establish the effect of cisternostomy on TBI outcomes.